Google Classroom Performance as Online Learning Media Arabic Lessons in MA Mambaul Ulum Megaluh - Miftakhul Rif'ah; Hilyah Ashoumi (SCHOOLAR: Social and Literature Study in Education, 2021)
This study aims to describe the performance of Google Classroom as an online learning medium for Arabic subjects in class XI MA Mambaul Ulum Megaluh. This research method uses data collection techniques in the form of interviews and questionnaires. The data analysis technique is through the use of qualitative calculations with a Likert scale. However, the results of this study show that learning through Google Classroom has a bad impact. This can be seen from the results of the questionnaire regarding the feasibility of the google classroom learning media which is considered less suitable for students to use. Meanwhile, on the learning performance side, students also stated that they were not happy with this application and were considered to be still difficult to understand the plot.